Sectoral Tax Justice and Global Value Chains: Evidence from Indonesia’s Resource and Digital Sectors (Indonesian Tax Justice Review, 2025)
Global value chains shape how profits are distributed across jurisdictions. This paper compares tax justice outcomes in Indonesia’s mining, palm oil, and digital sectors. Using comparative sectoral analysis, the study examines how value chain positioning affects taxing rights. The findings reveal systematic disadvantages for source countries. The global contribution of this study lies in integrating sectoral analysis into tax justice discourse. Indonesia’s experience offers insights for rethinking taxation in globalized production systems.